A Protocol for a Pan-Canadian Prospective Observational Study on Active Surveillance or Surgery for Very Low Risk Papillary Thyroid Cancer - Sawka, Anna M.; Ghai, Sangeet; Tomlinson, George; Baxter, Nancy N.; Corsten, Martin; Imran, Syed Ali; Bissada, Eric; Lebouef, Rebecca; Audet, Nathalie; Brassard, Maryse; Zhang, Han; Gupta, Michael; et al. (Frontiers in Endocrinology, 2021)
Background: The traditional management of papillary thyroid cancer (PTC) is thyroidectomy (total or partial removal of the thyroid). Active surveillance (AS) may be considered as an alternative option for small, low risk PTC. AS involves close follow-up (including regularly scheduled clinical and radiological assessments), with the intention of intervening with surgery for disease progression or patient preference. Methods: This is a protocol for a prospective, observational, long-term follow-up multi-centre Canadian cohort study. Consenting eligible adults with small, low risk PTC (< 2cm in maximal diameter, confined to the thyroid, and not immediately adjacent to critical structures in the neck) are offered the choice of AS or surgery for management of PTC. Patient participants are free to choose either option (AS or surgery) and the disease management course is thus not assigned by the investigators. Surgery is provided as usual care by a surgeon in an institution of the patient’s choice. Our primary objective is to determine the rate of ‘failure’ of disease management in respective AS and surgical arms as defined by: i) AS arm – surgery for progression of PTC, and ii) surgical arm - surgery or other treatment for disease persistence or progression after completing initial treatment. Secondary outcomes include long-term thyroid oncologic and treatment outcomes, long-term surgical complications, and patient-reported outcomes. Discussion: The results from this study will provide long-term clinical and patient reported outcome evidence regarding active surveillance or immediate surgery for management of small, low risk PTC. This will inform future clinical trials in disease management of small, low risk papillary thyroid cancer. Registration details: This prospective observational cohort study is registered on clinicaltrials.gov (NCT04624477), but it should not be considered a clinical trial as there is no assigned intervention and patients are free to choose either AS or surgery.